Oral immunization with recombinant Streptococcus lactis carrying the Streptococcus mutans surface protein antigen gene. - Iwaki, M (1990)
A recombinant Streptococcus lactis strain which carries the structural gene for a surface protein antigen (PAc) of 190,000 daltons from Streptococcus mutans serotype c was constructed for development of an oral vaccine against dental caries. The gene from S. mutans MT8148 joined to shuttle vector pSA3 was successfully transformed into S. lactis IL1403. A small amount of PAc was detected in the cell homogenate and cytoplasmic fraction of the recombinant S. lactis, but not in the culture supernatant of the recombinant, by Western immunoblotting and dot immunoblotting. The level of PAc-specific mRNA in the recombinant strain was lower than that in S. mutans MT8148. However, significant salivary immunoglobulin A and serum immunoglobulin G responses to PAc were induced in mice immunized orally with the recombinant S. lactis.